Do we need invasive confirmation of cardiac magnetic resonance results? - Siastała, Paweł; Kądziela, Jacek; A. Małek, Łukasz; Śpiewak, Mateusz; Lech, Katarzyna; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Coronary artery revascularization is indicated in patients with documented significant obstruction of coronary blood flow associated with a large area of myocardial ischemia and/or untreatable symptoms. There are a few invasive or noninvasive methods that can provide information about the functional results of coronary artery narrowing. The application of more than one method of ischemia detection in one patient to reevaluate the indications for revascularization is used in case of atypical or no symptoms and/or borderline stenosis. Aim : To evaluate whether the results of cardiac magnetic resonance need to be reconfirmed by the invasive functional method. Material and methods : The hospital database revealed 25 consecutive patients with 29 stenoses who underwent cardiac magnetic resonance (CMR) and fractional flow reserve (FFR) between the end of 2010 and the end of 2014. The maximal time interval between CMR and FFR was 6 months. None of the patients experienced any clinical events or underwent procedures on coronary arteries between the studies. Results: According to the analysis, the agreement of CMR perfusion with the FFR method was at the level of 89.7%. Assuming that FFR is the gold standard in assessing the severity of stenoses, the sensitivity of CMR perfusion was 90.9%. The percentage of non-severe lesions which were correctly identified in CMR was 88.9%. Conclusions : The study shows that CMR perfusion is a highly sensitive method to detect hemodynamically significant CAD and exclude nonsevere lesions. With FFR as the reference standard, the diagnostic accuracy of MR perfusion to detect ischemic CAD is high.